Abnormal Levels of Metal Micronutrients and Autism Spectrum Disorder: A Perspective Review - Behl, Supriya; Mehta, Sunil; Pandey, Mukesh K. (Frontiers in Molecular Neuroscience, 2020)
The aim of the present review is to summarize the prevalence of abnormal levels of various metal micronutrients including copper (Cu), iron (Fe), magnesium (Mg), zinc (Zn), and selenium (Se) in Autism Spectrum Disorder (ASD) using hair, nail and serum samples. A correlation of selected abnormal metal ions with known neurodevelopmental processes using Gene Ontology (GO) term was also conducted. Data included in this review are derived from ASD clinical studies performed globally. Metal ion disparity data is also analyzed and discussed based on gender (Male/Female) to establish any gender dependent correlation. Finally, a rational perspective and possible path to better understand the role of metal micronutrients in ASD is suggested.